Association between polyunsaturated fatty acids and depression in women with infertility: a cross-sectional study based on the National Health and Nutrition Examination Survey - Hong, Yan; Jin, Xia; Shi, Lihong (Frontiers in Psychiatry, 2024)
Background Identifying possible influencing factors is crucial for the depression symptoms of women experiencing infertility. This study aims to explore the association between polyunsaturated fatty acids (PUFAs) and the odds of depression symptoms in women experiencing infertility. Methods This is a cross-sectional study based on the National Health and Nutrition Examination Survey (NHANES). PUFA intake was obtained through a 24-h dietary recall interview. Depression symptoms were defined using the Patient Health Questionnaire-9 (PHQ-9) with a score of ≥10 points or as taking antidepressants. The association between PUFA and depression was assessed using a logistic regression model by calculating the odds ratio (OR) with 95% confidence interval (CI). Subgroup analysis was carried out based on menopausal status and female hormone use. Results There were 725 participants included for analysis. After adjusting the covariables, lower odds of depression symptoms were found in patients with the intake of omega-3 PUFA (OR = 0.48, 95% CI: 0.24–0.96) and omega-6 PUFA (OR = 0.24, 95% CI: 0.14–0.42) in the second tertile (T2) in comparison to the first tertile (T1). The intake of α-linolenic (ALA) (OR = 0.48, 95% CI: 0.23–0.97) and linoleic acid (OR = 0.24, 95% CI: 0.14–0.41) in T2 was also found to be related to the reduced odds of depression symptoms in comparison to T1. Conclusions Our findings suggest a potential association between moderate omega-3 and omega-6 PUFA intake and a reduced risk of depression symptoms in women experiencing infertility. This implies that clinicians might find it useful to consider dietary advice that includes PUFA-rich foods as part of a broader strategy to address mental health in this patient group. However, further research is needed to confirm these preliminary findings and to establish the optimal levels of PUFA intake for mental health benefits.